Peningkatan Minat dan Prestasi Belajar Siswa Kelas 5 SD Negeri 2 Mujing melalui Game-based Learning Model - Puspitasari, Indah; Apriyanti, Chusna; Elvita, Nia; Irawati, Desi (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2024)
This research aims to develop and evaluate a game-based learning model as an effort to increase the interest and learning achievement of grade 5 students at SD Negeri 2 Mujing. The research method used is Class Action Research (CAR). This research involves active participation of students in using this learning model. The research results show that the game-based learning model significantly increases students' interest in learning, measured through participatory observation and questionnaires. Apart from that, there was an increase in student learning achievement as measured through initial, formativee and summative knowledge tests. These findings provide a positive contribution to the development of innovative learning strategies at the elementary school level, especially at SD Negeri 2 Mujing.